Coronary sinus size and ischemia improvement after reducer implantation; "one size to fit them all?". Issue 3 (14th April 2021) - Tzanis, Georgios; Khokhar, Arif A; Ponticelli, Francesco; Gallone, Guglielmo; Palmisano, Anna; Esposito, Antonio; Beneduce, Alessandro; Guarracini, Stefano; Colombo, Antonio; Giannini, Francesco
Abstract: Aim: Coronary sinus (CS) reducer implantation is associated with symptomatic relief of patients with refractory angina. However, 15% to 30% of the patients do not respond to this treatment. Aim if this study was to evaluate the effect of CS size in the effectiveness of the device. Methods: Prior to device implantation and at 4‐month resting ventricular function was assessed by stress cardiac magnetic resonance. Ischemia was assessed by the myocardial perfusion reserve index (MPRI). Results: Fifteen patients (66 ± 10 years) underwent successful CS Reducer implantation, with improvements in angina class and exercise tolerance. Patients with a smaller CS size (<5.8 mm) presented a significantly higher percentage increase in MPRI (63 ± 51 vs 9 ± 30%, P = .03) and a higher reduction in left ventricle end‐diastolic volumes. Conclusions: Greater benefits, in terms of ischemia improvement, after CS Reducer implantation were seen in patients with smaller CS sizes, suggesting a potential mechanism underlying the observed rates of reducer non‐responsiveness.